Fiscal Revenue and Capital Expenditure in West Lombok Regency: Evidence from 2012-2021 - Siti Aminah; Serkan Dilek; Douglas Chiguvi (Tinta Emas Publisher, 2026)
Fiscal decentralization is expected to strengthen local governments' capacity to convert fiscal resources into development-oriented public expenditure. However, increases in local revenue and intergovernmental transfers do not always translate into higher capital expenditure when local budgets are constrained by operational spending, rigid transfer rules, and macro-fiscal shocks. This study examines the effect of local own-source revenue (Pendapatan Asli Daerah/PAD), revenue-sharing funds (Dana Bagi Hasil/DBH), general allocation funds (Dana Alokasi Umum/DAU), and specific allocation funds (Dana Alokasi Khusus/DAK) on capital expenditure in West Lombok Regency, Indonesia, during 2012-2021. Using annual budget realization data and multiple linear regression estimated with EViews 13, the study evaluates both partial and simultaneous effects and reports diagnostic tests for normality, multicollinearity, heteroskedasticity, and autocorrelation. The model is statistically significant (Prob. F-statistic = 0.002202) and explains 94.68% of the variation in capital expenditure. PAD has a positive and significant effect on capital expenditure (coefficient = 0.948; p = 0.020), indicating that locally generated fiscal capacity expands space for development spending. DBH has a negative and significant effect (coefficient = -4.133; p = 0.019), suggesting that revenue sharing during the study period may have been absorbed by non-capital fiscal priorities. DAU is negative but statistically insignificant, while DAK is positive but insignificant at the 5% level. Diagnostic tests show normally distributed residuals and no evidence of multicollinearity or heteroskedasticity, although serial correlation is detected. The findings highlight the need to improve the quality of regional fiscal allocation by linking revenue growth and transfers to medium-term public investment priorities.